Valuing of knowledge in organizations and its embedding into organizational practices and routines - Cherman, Andréa; Rocha-Pinto, Sandra Regina (Review of Business Management, 2016)
Purpose – This study aims to analyze the impact of the different ways in which organizational members perceive and experience valuing of knowledge within the work context on its subsequent embedding into organizational routines. Design/methodology/approach – The phenomenographic method was applied, using in-depth semi-structured interviews for data collection. The intentional sample comprised twenty-two human resource professionals. Findings – The structural context, which the organization is part of, creates the social and spatial context that shapes a structuring pattern. This pattern establishes the way people consider knowledge of value and act to embed it into organizational practices and routines. Originality/value – The study reveals the relevance of contemporary organizational structures and forms – cooperatives, hybrid and social business; holacratic or entrepreneurial models; collaborative or partnership networks for innovation – that promote the use and embedding of individual knowledge into organizational routines and practices.